Hurricane Sandy’s flood frequency increasing from year 1800 to 2100 - Lin, Ning (2019)
Coastal flood hazard varies in response to changes in storm surge climatology and the sea level. Here we combine probabilistic projections of the sea level and storm surge climatology to estimate the temporal evolution of flood hazard. We find that New York City’s flood hazard has increased significantly over the past two centuries and is very likely to increase more sharply over the 21st century. Due to the effect of sea level rise, the return period of Hurricane Sandy’s flood height decreased by a factor of ∼3× from year 1800 to 2000 and is estimated to decrease by a further ∼4.4× from 2000 to 2100 under a moderate-emissions pathway. When potential storm climatology change over the 21st century is also accounted for, Sandy’s return period is estimated to decrease by ∼3× to 17× from 2000 to 2100.